The Relevance of the Interpretation of The Qurâ€™an with Qaul Al-á¹¢aá¸¥Äbah as a source of Islamic law in the current era - Maghfirah, Maghfirah; Zulkifli, Zulkifli (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
The interpretation of the Qurâ€™an with Qaul al-á¹£aá¸¥Äbah is a product of classical scholars. Interpretation with Qaul al-á¹£aá¸¥Äbah is considered as a very representative explanation of the truth of the understanding of the Qurâ€™an because they are still meeting with the Prophet Muá¸¥ammad so that there are not many deviations. But this method of interpretation is often forgotten in the writing of tafsÄ«r. Therefore, the purpose of this study is to analyze the process of interpretation of the Qurâ€™an conducted by á¹£aá¸¥Äbah. This article is a research library with a descriptive approach to collect documentation data from various articles, books then analyzed by content analysis. The results of this research are the strengths of TafsÄ«r al-á¹¢aá¸¥Äbah are that they are neutral regardless of political interests or schools of thought, are free from the history of isrÄâ€™iliyyÄt, and no difference. While its weakness is not yet interpreted broadly and in detail, it is still partial and free of critical nature. In some instances in the current era, it is possible to make laws based on Qaul al-á¹£aá¸¥Äbah as one of the sources of Islamic law. The similarity of this research with previous research is to discuss the interpretation of Qaul al-á¹¢haá¸¥Äbah, including the characteristics and instruments and examples of interpretations of the Qurâ€™an carried out by á¹¢aá¸¥Äbah, such as Ibnâ€™ AbbÄs, Ibn MasÊ»Å«d, â€˜Ä€isyah, AbÅ« Hurairah and â€˜AlÄ« bin AbÄ« á¹¬Älib. While the difference is this research found the strengths and weaknesses of the interpretation of Qaul al-á¹¢haá¸¥Äbah. In the discussion, this article also analyzes Qaul al-á¹¢haá¸¥Äbah as a source of Islamic law in the current era